2022
DOI: 10.3390/life12030378
|View full text |Cite
|
Sign up to set email alerts
|

How to Treat HR+/HER2- Metastatic Breast Cancer Patients after CDK4/6 Inhibitors: An Unfinished Story

Abstract: CDK4/6 inhibitors in association with endocrine therapy represent the best therapeutic choice for either endocrine-sensitive or resistant hormone-receptor-positive advanced breast cancer patients. On the contrary, the optimal therapeutic strategy after the failure of CDK4/6 inhibitors-based treatment still remains an open question worldwide. In this review, we analyze the most studied mechanisms of resistance to CDK4/6 inhibitors treatment, as well as the most significant results of retrospective and prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Targeted therapy aims to deliver drugs to specific genes or proteins that are found only in cancerous cells or in the tissue microenvironment that is driving tumor growth. It is often used in combination with other types of cancer treatment, such as chemotherapy [13,21,71]. Targeted therapy involves developing drugs that inhibit cancer proliferation, promote cell cycle regulation, induce apoptosis or autophagy, or deliver harmful substances only to cancer cells to eliminate them [72].…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted therapy aims to deliver drugs to specific genes or proteins that are found only in cancerous cells or in the tissue microenvironment that is driving tumor growth. It is often used in combination with other types of cancer treatment, such as chemotherapy [13,21,71]. Targeted therapy involves developing drugs that inhibit cancer proliferation, promote cell cycle regulation, induce apoptosis or autophagy, or deliver harmful substances only to cancer cells to eliminate them [72].…”
Section: Targeted Therapymentioning
confidence: 99%
“…Despite various screening programs aimed at reducing tumor incidence, numerous cancer cases are diagnosed at advanced stages, making surgical removal impossible. Current cancer therapies face several challenges related to their selectivity, specificity, complexity, side effects, and most importantly, drug resistance [12,13]. Considering these factors, it is crucial to continue making ongoing efforts to reassess therapeutic approaches and develop more efficient cancer medications that can overcome these existing obstacles [14].…”
Section: Introductionmentioning
confidence: 99%
“…The continuation of CDK4/6 inhibitor beyond progression remains controversial given the conflicting data discussed above [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. This approach is not standard clinical practice and the mentioned research studies are likely to provide more information about the efficacy of this approach and on patient selection.…”
Section: How To Approach a Patient With Hormone Receptor Positive Mbc...mentioning
confidence: 99%
“…PFS on first line CDK4/6 inhibitor ranges from 2–3 years; however, the median OS of about five years suggests limited efficacy of subsequent anti-cancer treatments. For instance, several recent trials have shown that fulvestrant achieves a median PFS of 2–3 months after progression to CDK4/6 inhibitors, warranting the development of better treatment strategies to extend the endocrine treatment window before moving to cytotoxic chemotherapy [ 19 , 20 , 21 ] Importantly, in the past few years, the mechanisms of resistance to CDK4/6 inhibitors and endocrine therapy are starting to be unraveled, allowing for an expansion in the pipeline of effective agents in this setting [ 22 , 23 ]. Multiple randomized phase 2 and 3 trials have recently reported positive results, leading to significant changes in treatment algorithms for HR-positive MBC.…”
Section: Introductionmentioning
confidence: 99%
“…Following ET + CDK4/6i progression, limited data compared standard treatments with chemotherapy ( Figure 2 ). Cogliati et al reviewed these experiences and concluded that continuing CDK4/6i or switching to another CDK4/6i can remain effective post-progression ( 22 ). Additionally, ‘chemotherapy-like’ treatments like antibody-drug conjugates (ADCs) such as trastuzumab-deruxtecan (T-DXd) and sacituzumab-govitecan (SG) expand treatment options for HR-resistant and HER2 − low/negative MBC ( 23 , 24 ).…”
mentioning
confidence: 99%